Keterlekatan Etika Kewirausahaan Perempuan Penenun pada Struktur Sosial Etnik Bugis di Sulawesi Selatan - Syukur, Muhammad; Akhmad, Akhmad (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2023)
Loom development and the entry of the market economy system into the socio-economic system of weavers create three weaver groups with different entrepreneurial ethics. This research aims to describe the differences in entrepreneurial ethics of weaver women in South Sulawesi so that they could survive from market economy system penetration. The research uses a qualitative approach. The data collection method is conducted through in-depth interviews, observation, and focus group discussion. Data analysis consists of three steps, namely, data reduction, data presentation, and conclusion drawing. The research results indicate that there are differences in entrepreneurial ethics between the three weaver groups. Gedogan (primitive loom) weavers have oversocialized entrepreneurial ethics, improved handloom (Alat Tenun Bukan Mesin) weavers have an entrepreneurial ethics between oversocialized and undersocialized, whilst weaving business women have an entrepreneurial ethics that is more towards undersocialized action. The strong embeddedness of entrepreneurial ethics in the oversocialized pole induces gedogan weavers as the strongest group in addressing price fluctuations and external interventions in textile production. A balanced embeddedness of entrepreneurial ethic between oversocialized and under socialized actions among the ATBM weavers makes them the most prone to failure in business due to limited capital, production, and network that makes them unable to compete with local weaving entrepreneurs at national and global levels. The embeddedness of weaving entrepreneurs' actions in the under socialized pole makes does not make to play a further role in economic activities, but their economic success is compensated by religiousness and social piety.